Хірургічна тактика за гострого калькульозного холециститу у хворих на цукровий діабет - Міщенко, В. В.; Пустовойт, П. І.; Осипенко, О. В.; Вододюк, Р. Ю. (Clinical Endocrinology and Endocrine Surgery, 2009)
156 patients concerning acute calculous cholecystitis on a background of the diabetes are operated. Preoperation fibroezophagogastroduodenoscopy — was obligatory. At the concomitant diseases the patients had the "syndrome of the mutual burdening" (SMB) of easy, middle and heavy degree. At the SMB І degree at patients with acute cholecystitis adhered to actively temporizing tactic and they were operated on 6-8 days. At the SMB ІІ-ІІІ degree the patients were operated after short-term preoperation preparation during 4-6 hours. Posteoperation lethality was 1,3%.The complications were observed at 25% patients.